Hubungan Pengetahuan dengan Kejadian Anemia: Fenomena Paradoks Pada Remaja Putri di Jakarta Timur - Wahyuni, Dwi; Widjayanti, Trisna Budy; Rusmiati, Desi (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2025)
Anemia among adolescent girls has long-term impacts on reproductive health and increases the risk of stunting in future generations. Although the government has provided school-based iron-folic acid (IFA) supplementation, anemia prevalence remains high and adherence to IFA intake is low. This study aimed to analyze the relationship between knowledge, nutritional status, and IFA adherence with anemia among adolescent girls, while also examining the paradoxical phenomenon in which higher levels of knowledge are accompanied by a persistently high prevalence of anemia. A cross-sectional design was conducted among 121 female students aged 15–18 years from two vocational high schools in East Jakarta. Data collected included hemoglobin levels, nutritional status, knowledge about anemia, and IFA adherence. Bivariate analysis was performed using Chi-square tests. The prevalence of anemia was 39.7%. Knowledge was significantly associated with anemia (p=0.007); however, adolescents with good knowledge had a higher proportion of anemia (54%) compared to those with poor knowledge (29.6%). Nutritional status and IFA adherence were not significantly associated. Compared with the 2023 Indonesia Health Survey, the prevalence in this study site was higher than the Jakarta average (±30%). Knowledge alone is insufficient to prevent anemia without behavioral changes and environmental support. School-based interventions should focus on behavioral modification, motivation, regular monitoring of IFA intake, and innovations in IFA taste and packaging to improve adolescent acceptability. These findings emphasize the need for cross-sectoral collaboration to reduce anemia prevalence among adolescent girls.